2022
DOI: 10.1108/qrom-07-2020-1982
|View full text |Cite
|
Sign up to set email alerts
|

Women's entrepreneurship at an older age: women linguists' hybrid careers

Abstract: PurposeThis study investigates how older women linguists' careers developed and led to self-employment, and this not necessarily in a linear career stage fashion. The focus is on understanding the factors that influence older women to become or continue into an entrepreneurship lifestyle, beyond economic reasons.Design/methodology/approachThe research questions that guided this research are: (1) How have women linguists' careers developed at older or older old age? and (2) Which factors influenced women lingui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 65 publications
0
0
0
Order By: Relevance
“…Römer-Paakkanen and Takanen-Körperich [34] studied older age women entrepreneurs and found that commitment to work and meaningful activities motivate entrepreneurs at an older age. Aging people may also have a combination of social, personal and financial reasons suitable for becoming an entrepreneur.…”
Section: Reasons For Becoming An Entrepreneur At An Older Agementioning
confidence: 99%
See 1 more Smart Citation
“…Römer-Paakkanen and Takanen-Körperich [34] studied older age women entrepreneurs and found that commitment to work and meaningful activities motivate entrepreneurs at an older age. Aging people may also have a combination of social, personal and financial reasons suitable for becoming an entrepreneur.…”
Section: Reasons For Becoming An Entrepreneur At An Older Agementioning
confidence: 99%
“…Figure 2.Factors that influence aging people to continue or start their self-employment[34], (Römer-Paakkanen and Takanen-Körperich modified from Allard[35] and Raivio and Karjalainen[36] (pp [15][16][17]…”
mentioning
confidence: 99%